2013
DOI: 10.11152/mu.2013.2066.151.jo1ugc2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided versus Computed Tomography-controlled facet joint injections in the middle and lower cervical spine: a prospective randomized clinical trial

Abstract: US-guided intra-articular injections show the same therapeutic effect as CT-guided intra-articular injections and result in a significant reduction of procedure duration without any exposure to radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 30 publications
1
37
0
2
Order By: Relevance
“…Sonographic treatment guidance has become established as an alternative method that also does not require radiation exposure or contrast agents. Like MRI compared to CT fluoroscopy, this allows significantly better soft tissue contrast and precise visualization of sensitive structures like the vertebral artery and is primarily suitable for injections in the lower cervical spine segments [41,42]. Exact guidance and localization of the injection cannula increases the safety for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Sonographic treatment guidance has become established as an alternative method that also does not require radiation exposure or contrast agents. Like MRI compared to CT fluoroscopy, this allows significantly better soft tissue contrast and precise visualization of sensitive structures like the vertebral artery and is primarily suitable for injections in the lower cervical spine segments [41,42]. Exact guidance and localization of the injection cannula increases the safety for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility and 1-year retrospective studies [31,33] all suggest significant utility of US-guidance for cervical nerve root injections. A recent RCT [22] evaluating the feasibility, accuracy and procedural time of USverus CT-guided injections demonstrated that US-guided approaches produced similar results in terms of accuracy and reduction in visual analog scores. In addition, US significantly reduced procedure time.…”
Section: Cervical Epidural Steroid Injectionsmentioning
confidence: 99%
“…It has been well established that US guidance is not only feasible but also clinically useful in the performance of cervical facet joint or medial branch blocks [20][21][22]. Galliano et al published a feasibility study using cadavers to assess US guidance for cervical facet injections.…”
Section: Cervical Facet Jointsmentioning
confidence: 99%
See 2 more Smart Citations